Immunodrugs: breaking B- but not T-cell tolerance with therapeutic anticytokine vaccines. - Link, A; Bachmann, M (2010)
Pathology in most chronic inflammatory diseases is characterized by an imbalance in cytokine expression. Targeting cytokines with monoclonal antibodies has proven to be a highly effective treatment. However, monoclonal antibody therapy has disadvantages such as high production costs, generation of antimonoclonal antibodies and the inconvenience of frequent injections. Therapeutic vaccines have the potential to overcome these limitations. The aim of active vaccination is to induce B-cell responses and obtain autoantibodies capable of neutralizing the interaction of the targeted cytokine with its receptor. In order to achieve this, therapeutic vaccines need to circumvent the potent tolerance mechanisms that exist to prevent immune responses against self-molecules. This article focuses on the tolerance mechanisms of the B- and T-cell compartments and how these may be manipulated to obtain high-affinity autoantibodies without inducing potentially dangerous autoreactive T-cell responses.